2016
DOI: 10.7554/elife.19695
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control of correlated intrinsic variability in cortical networks

Abstract: Cortical networks exhibit intrinsic dynamics that drive coordinated, large-scale fluctuations across neuronal populations and create noise correlations that impact sensory coding. To investigate the network-level mechanisms that underlie these dynamics, we developed novel computational techniques to fit a deterministic spiking network model directly to multi-neuron recordings from different rodent species, sensory modalities, and behavioral states. The model generated correlated variability without external no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 106 publications
9
78
0
Order By: Relevance
“…Our data are consistent with previous reports describing low-dimensional correlates of locomotion and arousal in visual cortex [5,[7][8][9][10][11][12][13][14], but suggest these results were glimpses of a much larger set of behavioral and cognitive variables encoded by ongoing activity patterns. We found that 16 dimensions of facial motor activity can predict 31% of the reliable spontaneous variance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data are consistent with previous reports describing low-dimensional correlates of locomotion and arousal in visual cortex [5,[7][8][9][10][11][12][13][14], but suggest these results were glimpses of a much larger set of behavioral and cognitive variables encoded by ongoing activity patterns. We found that 16 dimensions of facial motor activity can predict 31% of the reliable spontaneous variance.…”
Section: Discussionsupporting
confidence: 92%
“…Correlation with the first PC was positive or negative in approximately similar numbers of neurons (57% ± 6.7% SE positive), indicating that two large sub-populations of neurons alternate their activity ( Figure 1F). The slowness of these fluctuations implies a different underlying phenomenon to previously-studied "up and down phases" [3,12,[26][27][28], which alternate at a much faster timescale (100-300 ms instead of 10-20 s) and correlate with most neurons positively. Indeed, up/down phases could not even have been detected in our recordings, which scanned the cortex every 400 ms.…”
Section: Spontaneous Cortical Activity Reliably Encodes a High-dimensmentioning
confidence: 70%
See 2 more Smart Citations
“…experimental measurements have revealed relatively asynchronous firing, particularly in 21 vigilant and active behavioral conditions [16][17][18][19][20]. One of the most prominent theoretical 22 explanations of the asynchronous state, the so-called 'chaotic balanced state' hypothesis, 23 is based on balanced E and I [21][22][23][24].…”
mentioning
confidence: 99%